The Hidden Price of Plenty: Oxidative Stress and Calorie-Induced Cardiometabolic Dysfunction - Luka Komic; Marko Kumric; Jelena Komic; Marion Tomicic; Tina Ticinovic Kurir; Marko Grahovac; Marin Mornar; Doris Rusic; Josipa Bukic; Josko Bozic (Life)
Overnutrition is a predominant issue in contemporary society, increasing rapidly despite considerable progress in our comprehension of nutrition, the health consequences of different food categories, and the dangers linked to excessive calorie consumption. The pathways connecting obesity to associated disorders are intricate, although research has consistently identified oxidative stress as a principal facilitator of the progression of many diseases. In this paper, the synthesis of various reactive species at the molecular level is studied, and the influence of diet on their production is assessed, with a thorough examination of the cellular mechanisms involved. Furthermore, the correlation between oxidative stress and the development of cardiometabolic diseases is explored, highlighting the most recent and relevant research in the field.